On the Impact of UAS Contingencies on ATC Operations in Shared Airspace - Teutsch, J.; Petersen, C.C.; Schwoch, G.; Lieb, T.J.; Bos, T.J.J.; Zon, G.D.R. (IEEE, 2023)
In the near future, it is expected that an increasing number of Unmanned Aerial Systems (UAS) will operate at very low-level altitudes of up to 500 ft in urban and suburban areas. It is expected that these new airspace users will extend their operations and share available airspace with manned traffic. Dynamic Airspace Re-configuration (DAR) has been considered as one of the enablers for the integration of unmanned and manned traffic in such non-segregated airspace.The Royal Netherlands Aerospace Centre, NLR, together with their partners from the German Aerospace Centre, DLR, carried out simulations for the SESAR Industrial Research Project AURA that investigates requirements for an interface between Air Traffic Management (ATM) controlled airspace and highly automated U-space airspace for large numbers of unmanned aircraft. To this end, AURA defined the so-called AUSA, ATM U-space Shared Airspace, which is a generic type of airspace that can be delegated to contain both Air Traffic Control (ATC) and U-space controlled airspace volumes. The simulations carried out by NLR and DLR investigated U-space contingencies that could have an impact on those parts of the shared airspace controlled by ATC. This included specific UAS missions and related emergency and other contingency situations inside U-space that would require an extension into ATC controlled airspace. The simulations introduced the role of a manager for DAR processes. The DAR Manager received contingency requests from U-space and negotiated them with ATC.Results have shown that the introduced DAR Manager role and the designed working position supported and improved ATC operations. Negotiations between the DAR Manager and air traffic controllers, however, will only be possible if there is enough lead time - in the range of several minutes - to prepare for airspace changes. Emergency requests that require immediate action should be communicated to the affected controllers immediately by the system.